Microglial TNFα orchestrates protein phosphorylation in the cortex during the sleep period and controls homeostatic sleep. (16th November 2022) - Pinto, Maria J; Cottin, Léa; Dingli, Florent; Laigle, Victor; Ribeiro, Luís F; Triller, Antoine; Henderson, Fiona; Loew, Damarys; Fabre, Véronique; Bessis, Alain
Abstract: Sleep intensity is adjusted by the length of previous awake time, and under tight homeostatic control by protein phosphorylation. Here, we establish microglia as a new cellular component of the sleep homeostasis circuit. Using quantitative phosphoproteomics of the mouse frontal cortex, we demonstrate that microglia‐specific deletion of TNFα perturbs thousands of phosphorylation sites during the sleep period. Substrates of microglial TNFα comprise sleep‐related kinases such as MAPKs and MARKs, and numerous synaptic proteins, including a subset whose phosphorylation status encodes sleep need and determines sleep duration. As a result, microglial TNFα loss attenuates the build‐up of sleep need, as measured by electroencephalogram slow‐wave activity and prevents immediate compensation for loss of sleep. Our data suggest that microglia control sleep homeostasis by releasing TNFα which acts on neuronal circuitry through dynamic control of phosphorylation. Synopsis: Phosphorylation is a molecular determinant of homeostatic sleep control. Microglia, via the release of TNFα, control phosphorylation of proteins involved in sleep and regulate sleep homeostasis when sleep balance is challenged. Microglial TNFα modulates thousands of phosphorylation events in the cortex specifically during the light period, a phase of maximal sleep in mice. Substrates targeted by microglial TNFα comprise several phosphatases and kinases. Microglia‐specific deletion of TNFα in mice disrupts the phosphorylation of proteins important for sleep need and sleep duration at multiple phosphorylation sites. Microglial TNFα is required for the expression of sleep need and control of homeostatic sleep rebound following sleep deprivation. Abstract : This study reveals that microglia, via the release of TNFα, control phosphorylation of several proteins with known roles in sleep to maintain homeostatic sleep control.